Uma crítica da epistemologia da prática com base na categoria de totalidade - Gomes, Maria Regina Candelária (2009)
This research is of bibliographical matrix and on the basis of has as objective the critical one of the epistemology of practical the category of totality. The theoretical referential of the study is the historical materialism from authors Karel Kosik and Istiván Mészáros. It was intended to demonstrate that the knowledge is a totality and, therefore, the opposite the spalling. The objectives had been reached in the measure where the work if configures as a theoretical contribution for studies regarding the subject. The dissertation understands three chapters, beyond the introduction and of the conclusion.